Chitosan capped nickel oxide nanoparticles as a saturable absorber in a tunable passively Q-switched erbium doped fiber laser - Ahmad, Harith; Reduan, Siti Aisyah; Yusoff, Norazriena (Royal Society of Chemistry, 2018)
Nickel oxide (NiO) nanoparticles successfully prepared from a nickel(ii) chloride hexahydrate precursor are used to form a chitosan capped NiO nanoparticle thin film to serve as a saturable absorber (SA) for the generation of passively Q-switched pulses in an erbium doped fiber laser (EDFL). The NiO/chitosan SA based EDFL is able to generate stable pulsed outputs at a low threshold pump power of 104.90 mW with a central wavelength at 1562 nm. The highest pulse energy obtainable by the system is 15.30 nJ at a repetition rate of 42.66 kHz and a pulse duration of 2.02 μs. The laser has a spectral range of 58 nm from 1522 to 1580 nm, covering the C and L bands and even portions of the S band. This study experimentally demonstrates that the potential of the NiO/chitosan film as an SA material for Q-switching operations, combined with the biocompatibility, non-toxicity and high thermal resistance of Chitosan, holds great prospects for a broad range of applications.